“Big Data Analytics and Internet of Things (IoT): A Review” (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s techno savvy world everything is digitalized. Everything is on the tips of people. Trends are changing in seconds. The different trend in the current modern world is that all the devices used by common people are connected with the internet and the reason of this is to share the information or data without any human communication and improving the excellence of our daily lives. The purpose of this research was to provide understanding about big data analytics and Internet of Things (IoT).